Corporate social responsibility and financial performance: An empirical analysis of Indian banks - Shafat Maqbool; M. Nasir Zameer (Future Business Journal, 2018)
Despite scads research on the relationship between corporate social responsibility and financial performance, literature is still inconclusive. This study attempts to examine the relationship between corporate social responsibility and financial performance in the Indian context. Secondary data has been collected for 28 Indian commercial banks listed in Bombay stock exchange (BSE), for the period of 10 years (2007-16). The results indicate that CSR exerts positive impact on financial performance of the Indian banks. The finding of this study provides great insights for management, to integrate the CSR with strategic intent of the business, and renovate their business philosophy from traditional profit-oriented to socially responsible approach.
Keywords: 650; Content analysis; Corporate social responsibility; Panel data; Profitability; Stock returns